Analisis Kognitif dan Pemahaman Siswa Mengenai Pembelajaran IPA Pada Kelas 6C SDN 101766 Bandar Setia dengan Soal Berbasis HOTS - Ernita Pasaribu; Monica Intan Reni; Nadya Tesalonika Simbolon; Niko Alriadi Sinaga; Putri Nurul Auliya; Tetty Aprilya Rezeki Simatupang (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The implementation of Higher Order Thinking Skills (HOTS)-based questions in primary school education aims to enhance students' critical and creative thinking abilities. However, the biggest challenge in its implementation is how to assess and improve students' understanding of HOTS questions. This study aims to evaluate the understanding of 6-C grade students at SDN 101766 Bandar Setia regarding HOTS questions in Science and Social Studies (IPAS) learning, identify existing gaps in understanding, and provide recommendations for more effective teaching strategies. The research method used is direct observation complemented by a HOTS questionnaire consisting of five questions focused on students' abilities in analysis, evaluation, and creation. The study participants involved 17 students from grade 6-C who were observed in November 2024. The results showed that only 23.5% of students were able to answer the questions well, while the majority, 58.8%, did not understand the questions at all. The students with moderate understanding amounted to 17.7%. Based on these results, it is recommended that HOTS questions be introduced gradually, with improvements in teaching methods and the creation of a learning environment that supports the development of students' critical thinking skills.